La quête d’influence entre délibération, reconnaissance et valorisation - Olivier Voirol; Alexandre Dubuis (Communication)
Social science research on severe burns has brought to light the challenges people with skin injuries face regarding visibility in the public space. When affected individuals face the issues that come with self-exposure, they attempt to control their public appearance or how the public perceives burns. Drawing on semi-structured interviews and the study of a corpus of audiovisual content and social media, we highlight different modalities of public exposure to severe burns. Accentuated by the Internet, the plurality of exposure modes allows us to identify a typology of engaged postures (epistemic, recognition, appreciation) as well as pragmatic and normative tensions emerging between them. Due to the increased weight of digital technology, the posture of appreciation prevails over the other two, to the detriment of the public learning that is central to the quest for visibility of severe burn victims.